Exon junction complexes show a distributional bias toward alternatively spliced mRNAs and against mRNAs coding for ribosomal proteins - Hauer, Christian; Sieber, Jana; Schwarzl, Thomas; Hollerer, Ina; Curk, Tomaz; Alleaume, Anne-Marie; Hentze, Matthias W.; Kulozik, Andreas (Cell reports, 2016)
The exon junction complex (EJC) connects spliced mRNAs to posttranscriptional processes including RNA localization, transport, and regulated degradation. Here, we provide a comprehensive analysis of bona fide EJC binding sites across the transcriptome including all four RNA binding EJC components eIF4A3, BTZ, UPF3B, and RNPS1. Integration of these data sets permits definition of high-confidence EJC deposition sites as well as assessment of whether EJC heterogeneity drives alternative nonsense-mediated mRNA decay pathways. Notably, BTZ (MLN51 or CASC3) emerges as the EJC subunit that is almost exclusively bound to sites 20-24 nucleotides upstream of exon-exon junctions, hence defining EJC positions. By contrast, eIF4A3, UPF3B, and RNPS1 display additional RNA binding sites suggesting accompanying non-EJC functions. Finally, our data show that EJCs are largely distributed across spliced RNAs in an orthodox fashion, with two notable exceptions: an EJC deposition bias in favor of alternatively spliced transcripts and against the mRNAs that encode ribosomal proteins.
Gesehen am 07.05.2020